Venous Doppler in the Evaluation of Fetal Hydrops - C. Hofstaetter; S. Gudmundsson (Hindawi Limited, 2010)
Objective. To examine venous blood flow velocity in different types of fetal hydrops and its value in the prediction of outcome of pregnancies. Methods. Venous Doppler sonography was performed in 100 hydropic fetuses from 15 to 37 weeks of gestation. Blood velocity was recorded in the right hepatic vein (HV), the ductus venosus (DV) and in the intra-abdominal part of the umbilical vein (UV). Blood velocity indices were calculated and pulsations in the umbilical vein noted and grouped into a single, double or triple flow pattern. Blood velocity was related to cause of hydrops. Results. Mortality was noted in 51 cases of which 19 were by termination of pregnancy. Mortality in the 30 with normal venous blood velocity was 35%, but 58% in cases of abnormal Doppler. Abnormal HV and DV blood velocities were recorded in 39 and 34 cases, respectively and were strongly related to mortality (𝑃<.04 and 𝑃<.003, resp.). UV pulsations were noted in 49 fetuses and were significantly related to mortality (𝑃<.04). Mortality and abnormal venous velocities were most frequent in the low-output hydrops group (79% and 75%, resp.). Conclusions. Abnormal venous blood velocity is related to mortality in pregnancies complicated by fetal hydrops. Venous Doppler sonography should be a part of the routine work-up of pregnancies complicated by fetal hydrops.